Carbenoxolone-mediated cytotoxicity inhibits Vaccinia virus replication in a human keratinocyte cell line. Issue 1 (December 2018) - Haga, Ismar; Simpson, Jennifer; Hawes, Philippa; Beard, Philippa
Abstract The re-emergence of poxviral zoonotic infections and the threat of bioterrorism emphasise the demand for effective antipoxvirus therapies. Here, we show that carbenoxolone, a pharmacological inhibitor of gap junction function and a compound widely used in cell culture, is capable of hindering the replication ofVaccinia virus, the prototypical poxvirus, in a gap junction-independent manner in a human keratinocyte cell line. Viral protein synthesis occurs in the presence of carbenoxolone but infectious virion formation is minimal, indicating that carbenoxolone blocks viral morphogenesis. Initial viability tests suggested that carbenoxolone was not toxic to cells. However, electron microscopic analysis of carbenoxolone treated cells revealed that it alters the cellular endomembrane system. This widespread ultrastructural damage preventsVaccinia virus virion assembly. These results strengthen the need for thorough characterisation of the effects of antiviral compounds on the cellular ultrastructure.